Measuring Magnetic Field With Atacama Large Millimeter/Submillimeter Array - Loukitcheva, Maria (Frontiers in Astronomy and Space Sciences, 2020)
This article reviews the use of magnetic bremsstrahlung at short radio wavelengths to measure solar magnetic fields. The vertical component of the chromospheric magnetic field can be deduced from the observed polarization and brightness temperature spectrum at millimeter wavelengths. State-of-the-art 3D radiative magnetohydrodynamic (R-MHD) simulations of the quiet solar atmosphere were used to synthesize observational deliverables at the wavelengths of the Atacama Large Millimeter/Submillimeter Array (ALMA) and to test the applicability of the method. The article provides selected observational examples of the successful application of the method and presents an overview of the recent developments and potential of the magnetic field measurements with ALMA.